Potential for stratospheric Doppler windspeed measurements of Jupiter by sub-millimetre spectroscopy - Hurley, J; Irwin, P; Ellison, B; de Kok, R; Calcutt, S; Teanby, N; Fletcher, L; Irshad, R (2010)
The sub-millimetre/microwave range of the spectrum has been exploited in the field of Earth observation by many instruments over the years and has provided a plethora of information on atmospheric chemistry and dynamicshowever, this spectral range has not been fully explored in planetary science, having been exclusively employed to carry out ground-based measurements. To this end, a sub-millimetre instrument, the Orbiter Terahertz Infrared Spectrometer (ORTIS), is studied by the University of Oxford and the Rutherford Appleton Laboratory, to meet the requirements of the European Space Agency's Cosmic Visions 2015-2025 programme-in particular, the Europa Jupiter System Mission (EJSM), which has the European Space Agency and the National Aeronautics and Space Administration as partners. ORTIS is designed to measure atmospheric temperature, the abundance of stratospheric water vapour and other jovian gases, and is intended to be capable of retrieving vertical profiles of horizontal windspeed in the stratosphere for the first time, from Doppler-shifted emission lines measured at high spectral resolution. In this work, a preliminary study and implementation of the estimation of windspeed profiles on simulated spectra representative of Jupiter is presented, detailing the development of the retrieval algorithm, showing that a sub-millimetre instrument such as ORTIS should be able to retrieve windspeed profiles to an accuracy of about 15 m/s between 70 and 200 km/0.1-10 mb using a single near-limb measurement, for expected noise amplitudes. © 2010 Elsevier B.V.. All rights reserved.